The effect of increasing the gaps between the front teeth on torque and intrusion control of the incisors for anterior retraction with clear aligners: a prospective study - Ni Li; Xiao Lei; Yuan Cao; Lu Liu; Yanqi Zhang; Qiang Ning; Linyuan Gui; Fang Jin (BMC, 2024)
Abstract Objective To investigate the effect of sequential distalization on increasing gaps in the maxillary anterior teeth, focusing on the control of torque and three-dimensional teeth movement during anterior retraction with clear aligners in extraction cases. Methods We recruited 24 patients who were undergoing extraction bilateral maxillary first premolars with clear aligners. According to a predetermined increment in the spaces between the maxillary anterior teeth, the patients were divided into three groups: those with no gap (9 cases), a 0.5 mm gap (6 cases) and a 1.0 mm gap (9 cases). In each group, a 2.0 mm en-mass retraction was applied on the anterior teeth. Plaster casts of the upper full dentition were obtained both before and after a 2 mm retraction. The palatal folds were used to overlap each pair of models. The three-dimensional movement of the teeth and the change of torque for the anterior teeth were subsequently analyzed using Geomagic Studio 2014 software. Results The change in torque in the groups with added gaps was significantly smaller than that in the group with no gaps (P < 0.05). There was no significant difference in this respect when comparing the group with a 0.5 mm gap added to the group with a 1.0 mm gap was added (P > 0.05). In the labial-lingual and vertical directions, the displacements of the central and lateral incisors were smaller in the groups with additional gaps compared to those in the groups without gaps (P < 0.05). However, there was no significant difference observed when comparing the group with a 0.5 mm added gap to the group with a 1.0 mm added gap (P > 0.05). Then, a comparison was made between the displacement of the second premolar to the second molar in the mesial-distal direction across all groups. The study revealed that the anchorage molars in the group without gaps demonstrated significantly smaller displacement compared to those in the group with additional gaps (P < 0.05). Conclusion Advantages were observed in controlling the torque of the anterior teeth and achieving a desired pattern closer to normal bodily movement by sequentially distalizing the maxillary anterior teeth gaps. Increasing the gaps between the maxillary anterior teeth also resulted in improved control of the vertical direction of the anterior teeth. However, this retraction strategy necessitates substantial protection of the anchorage molars.